IMPLEMENTASI METODE PEMBELAJARAN AKTIF DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Hastuti (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to describe the implementation of active learning methods and their effect on improving the learning outcomes of Grade IV students at SD Negeri 8 Binamu, Jeneponto Regency, South Sulawesi. The low student learning outcomes caused by the dominance of conventional lecture methods served as the background for this research. This study employed a Classroom Action Research (CAR) approach conducted in two cycles using the Kemmis and McTaggart spiral model. The research subjects were 25 Grade IV students. Data were collected through observation, learning outcome tests, and documentation, then analyzed using descriptive qualitative and quantitative methods. The results showed that the application of active learning methods, including group discussion, question and answer, and project-based learning, significantly improved student learning outcomes. In the first cycle, classical completeness reached 64%, which then increased to 88% in the second cycle, exceeding the predetermined success indicator of 80%. Thus, the implementation of active learning methods has been proven effective in improving the learning outcomes of Grade IV students at SD Negeri 8 Binamu, Jeneponto Regency.